Electing women to Parliament: Fiji and the alternative vote electoral system - Rae Nicholl (Asia Pacific Network, 2006)
In many places in the world, women struggle to be heard and, when it comes to having a voice in the highest authority in the land, the difficulties in some countries can be almost insurmountable. Women in Fiji are confronting the problem of women’s representation in Parliament. With only a small number of women (7.04 percent) in the House of Representatives, what changes could the citizens of Fiji make to remedy this lack of female representation? One answer that could be considered is for Fijian lawmakers to make amendments to the alternative vote electoral system, a variation on preferential voting. The alternative vote falls into the same simple plurality category as first-past-the-post, a system notoriously unfriendly to women candidates.